Math for excellence / Norlida Othman and Siti Zaharah Mohd Ruslan - Othman, Norlida; Mohd Ruslan, Siti Zaharah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Math for Excellence is a workshop conducted for students in Diploma in Food Technology (AS116), Diploma in Textile and Clothing Technology (AS122), and Diploma of Halal Management (IC120). The objective of this workshop is to empower students with the technique of answering final examination questions for courses Pre-Calculus (MAT133), and Business Mathematics (MAT112). Both of these courses are considered difficult courses with a high failure rate. 101 students attended the workshop that was conducted at UiTM Kuala Pilah on June 16, 2023, that aimed to improve student performance and reduce failure rate.